Modeling of the operation conditions on the gas purging performance of polymer electrolyte membrane fuel cells. (20th April 2017) - Mu, Yu-Tong; He, Pu; Ding, Jing; Tao, Wen-Quan
Abstract: Gas purging has been a common and favorable strategy to improve the cold-start possibility of a polymer electrolyte membrane fuel cell (PEMFC). In the present study, water removal processes in a PEMFC during the gas purging prior to its shutdown are numerically investigated with a transient two-fluid model. The dryness in the sub-regions of the PEMFC is analyzed. Effects of the operation conditions (such as the gas flow rate, relative humidity and temperature) are also explored. The results indicate that water removal processes are not sequential and the main drying mechanism in the porous medium is the surface evaporation under the pendular stage. The overall dryness highly depends on the inlet water flux other than the convective water flux under the same gas flow rate. The operation parameters have a significant impact on the overall drying performance in terms of the purging effectiveness and the energy consumption. Highlights: Water removal processes during the gas purging are numerically developed. Dryness in the sub-regions of PEM fuel cell is analyzed. Surface evaporation is the main drying mechanism in the porous medium. The overall inlet water flux other than the convective water flux dominates. Effects of the operation conditions on the purging effectiveness are explored.